The effect of peer feedback on EFL students writing performance: A case at an upper secondary school - Nguyễn Văn Son (Trường Đại học Trà Vinh, 2021)
When talking about self-assessment, Falchikov (as cited in Topping, 2010) found that younger students seemed to be less reliable when working on their own. Better students tended to undermark their work and average ones tended to overmark themselves. Therefore, this study attempted to address this problem and is based on the idea of student-centered instruction and it has come to the investigation of peer’s value in pair and group work so that peer feedback is maximized. When applying peerfeedback, the classroom teacher sees each individual’s work as a process not a product and this process has to be scaffolded by either their teacher or classmates. This view is also about true learning, which means learning happens when they have something to show or something to remind each other; something they can share, think carefully to contribute to the accomplishment of work. After this process, it can be affirmable that they would have a more accomplished product with appropriate strategies. When this view of peer-feedback is fostered, more advantages can be seen. When working in pairs or groups, students feel more secured and therefore less tense. Working with others help more timid learners who seem to be less involved in the whole class work to engage in group discussion. What is more, working with others help individuals raise their awareness of team spirit and thus bringing about class unity. Furthermore, the classroom will become more exciting with group or pair discussion than just a monotonous classroom with a font-teacher talking all the time.